2016
DOI: 10.3961/jpmph.16.005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Educational Status on 10-Year (2004-2014) Cardiovascular Disease Prognosis and All-cause Mortality Among Acute Coronary Syndrome Patients in the Greek Acute Coronary Syndrome (GREECS) Longitudinal Study

Abstract: Objectives:The association between educational status and 10-year risk for acute coronary syndrome (ACS) and all-cause mortality was evaluated.Methods:From October 2003 to September 2004, 2172 consecutive ACS patients from six Greek hospitals were enrolled. In 2013 to 2014, a 10-year follow-up (2004-2014) assessment was performed for 1918 participants (participation rate, 88%). Each patient’s educational status was classified as low (<9 years of school), intermediate (9 to 14 years), or high (>14 years).Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
2
5
1
2
Order By: Relevance
“…The US National Bureau of Economic Research stated that each additional 4 years of education lowered all-cause mortality by almost 1.8% and reduced the risk of heart disease by 2.2%. 17 The present study found that the relationship between education and hypertension was a Bell-shaped pattern ( Table 3 ), showing people who attained a middle school education had a 53.5% higher risk for having hypertension (95% CI, 1.074–2.194; P =0.019) than those who attained college education. People who did not surpass primary school generally took part in more physically active jobs, which might cause them to have a lower incidence of coronary heart disease than among those whose jobs required little or no physical activity.…”
Section: Discussionsupporting
confidence: 47%
“…The US National Bureau of Economic Research stated that each additional 4 years of education lowered all-cause mortality by almost 1.8% and reduced the risk of heart disease by 2.2%. 17 The present study found that the relationship between education and hypertension was a Bell-shaped pattern ( Table 3 ), showing people who attained a middle school education had a 53.5% higher risk for having hypertension (95% CI, 1.074–2.194; P =0.019) than those who attained college education. People who did not surpass primary school generally took part in more physically active jobs, which might cause them to have a lower incidence of coronary heart disease than among those whose jobs required little or no physical activity.…”
Section: Discussionsupporting
confidence: 47%
“…Association between CVD risks and As exposure could vary by age, gender, smoking status, alcohol consumption, physical activity, diabetes and obesity status, education level as well as some other socio-economic factors, all of which might be either powerful predictors of CVD risks or important factors in As toxicity [86][87][88][89][90][91][92][93][94]. However, varied adjustment for these well-identified potential confounders could be observed among different studies, leading to different magnitudes of associations estimated when combined in a meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Chinese patients with better hypertension awareness prefer large hospitals with better medical quality [29,30]. Therefore, well-educated patients were more likely to use outpatient services in tertiary hospitals instead of primary healthcare institutions due to their preference for high-quality medical service and better financial status [50]. Actually, one-third of hypertensive patients visiting outpatient units in tertiary hospitals have reasonable blood pressure control and thus waste limited medical resources [29].…”
Section: Discussionmentioning
confidence: 99%